Strategi Perubahan Perilaku Masyarakat pada Masa Pandemi COVID-19 Melalui Bidang Penyiaran - Aris Tristanto; Azani Maizuar (Jurnal Studi Inovasi, 2022)
The broadcasting sector is one way to encourage changes in people's behavior because the broadcasting sector has the power to influence the community so that people see that what is conveyed by the broadcasting sector is the truth. This paper is literal or literature (library research). The technique of collecting data and information is done by reviewing written sources. In encouraging changes in people's behavior during the broadcasting pandemic, activities such as: 1) Socializing the prevention of the corona virus based on local culture; 2) Make an appeal to the community using simple language; 3) Campaign by involving traditional leaders and other community leaders. In this paper, the author gives recommendations to the broadcasting sector, if you want to know the extent to which the final achievements related to the broadcasting sector in shaping people's behavior changes during the COVID-19 pandemic can be seen from three aspects, namely cognitive aspects, affective aspects and the three conative aspects.